PENERAPAN ASAS-ASAS KEPATUTAN DALAM PERJANJIAN ASURANSI (STUDI KASUS PUTUSAN NOMOR 70/PDT.G/2023/PN_BLG) - Anriyani, Dian; Sumanto, Listyowati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: The purpose of this research is to analyze the application of the principle of propriety in insurance agreements that contain clauses to exclude the insurer from all legal obligations and responsibilities, the principle of propriety in insurance agreements, this is based on the inherent principle of propriety in the dimensions of the insurance agreement aspect, and insurance cannot guarantee its own damage. The research method used is normative legal research, descriptive in nature. Secondary data is analyzed qualitatively. Conclusions are drawn using deductive logic. Identification of the problem (1) How is the regulation of the principle of propriety in insurance agreements in terms of the Civil Code, (2) how is the principle of propriety applied by the Judge as one of the considerations in Decision Number 70/pdt.G/2023/PN_ Blg. In making an agreement, it is known that there is freedom of contract, but in the implementation of an insurance agreement, an agreement should be made by applying the principle of propriety because if it is not in accordance with the principle of propriety, a legal dispute arises, then the judge in legal considerations can add or set aside the contents of the agreement that are not appropriate in the agreement: the parties involved in the insurance agreement should be careful in their actions, obligations can be born due to agreements and laws, but in agreements there can be defaults made by the parties. Keywords: default, principle of propriety, agreement